Biological Air Contamination in Elderly Care Centers: Geria Project - Aguiar, L. (2015)
Indoor air quality (IAQ) affects health particularly in susceptible individuals such as the elderly. It has been estimated that the older population spends approximately 19–20 h/d indoors, and the majority of the elderly spend all of their time indoors in elderly care centers (ECC). Older individuals may be particularly at risk of exposure to detrimental effects from pollutants, even at low concentrations, due to common and multiple underlying chronic diseases that increase susceptibility. This study, aimed to assess the impact of indoor biological agents in 22 ECC located in Porto, was conducted during summer and winter from November 2011 to August 2013 at a total of 141 areas within dining rooms, drawing rooms, medical offices, and bedrooms (including the bedridden). Air sampling was carried out with a microbiological air sampler (Merck MAS-100) and using tryptic soy agar for bacteria and malt extract agar for fungi. The results obtained were compared with the recently revised Portuguese standards. In winter, mean fungi concentration exceeded reference values, while bacteria concentrations were within the new standards in both seasons. The main fungi species found indoors were Cladosporium (73%) in summer and Penicillium (67%) in winter. Aspergillus fumigatus, Aspergillus niger, and Aspergillus flavus, known potential pathogenic/toxigenic species, were also identified. Although the overall rate and mean values of bacteria and fungi found in ECC indoor air met Portuguese legislation, some concern is raised by the presence of pathogenic microorganisms. Simple measures, like opening windows and doors to promote air exchange and renewal, may improve effectiveness in enhancing IAQ.